2020
DOI: 10.1155/2020/3852431
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Effects of Weekly Supragingival Irrigation with Aerosolized 0.5% Hydrogen Peroxide and Formation of Cavitation Bubbles in Gingival Tissues after This Irrigation: A Six-Month Randomized Clinical Trial

Abstract: Introduction. The study investigated the effect of weekly supragingival irrigation with aerosolized 0.5% hydrogen peroxide (H2O2) solution as a maintenance periodontal therapy on clinical and microbiological parameters in patients with chronic periodontitis. The other purpose was to investigate whether cavitation bubbles can penetrate not only into periodontitis-damaged tissues but also into ex vivo porcine healthy periodontal tissues. Materials and Methods. The study included 35 systemically healthy patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The papilla bleeding index (using a periodontal probe) was determined as an index of gingival inflammation. Periodontal condition was assessed using periodontal probing depth, bleeding on probing, and classification of clinical attachment loss [none/mild periodontitis, moderate periodontitis (interproximal sites of 2 mm or more, with clinical attachment loss of 4 mm or more, not on the same tooth, or interproximal sites of 2 mm or more, with probing depth of 5 mm or more); severe periodontitis (interproximal sites of 2 mm or more, with clinical attachment loss of 6 mm or more on different teeth, or interproximal site of 1 mm or more, with the probing depth of 5 mm or more] [7,15]. The clinical examinations were carried out by dentists with minimum experience of 3 years, and they were naïve to the immunosuppressive therapies used.…”
Section: Clinical Dental Examinationmentioning
confidence: 99%
“…The papilla bleeding index (using a periodontal probe) was determined as an index of gingival inflammation. Periodontal condition was assessed using periodontal probing depth, bleeding on probing, and classification of clinical attachment loss [none/mild periodontitis, moderate periodontitis (interproximal sites of 2 mm or more, with clinical attachment loss of 4 mm or more, not on the same tooth, or interproximal sites of 2 mm or more, with probing depth of 5 mm or more); severe periodontitis (interproximal sites of 2 mm or more, with clinical attachment loss of 6 mm or more on different teeth, or interproximal site of 1 mm or more, with the probing depth of 5 mm or more] [7,15]. The clinical examinations were carried out by dentists with minimum experience of 3 years, and they were naïve to the immunosuppressive therapies used.…”
Section: Clinical Dental Examinationmentioning
confidence: 99%
“…The water jet-induced cavitation bubble, recognized for its extensive impact range, high efficiency, and eco-friendliness, is extensively utilized in ship maintenance and chemical equipment cleaning [1][2][3][4][5][6]. In medicine, ultrasound-induced cavitation bubbles are used in cancer treatment, stone crushing, and gingival surgery owing to their small impact area and large impact force [7][8][9]. In recent years, with the development of laser technology, it has been found that a cavitation bubble will emerge between the laser and liquid medium.…”
Section: Introductionmentioning
confidence: 99%